Enhanced study of facial soft tissues using a novel large scale histology technique. Issue 1 (17th August 2022) - Minelli, Lennert; Bown, Rory George Charles; Mu, Erica Wung Hwa; Whitehead, Darryl Lane; Henderson, Tania Helen; Lawrence, Felicity; Mellor, Ian; Wissemann, Matthew Ian; Brown, Cameron Peter; van der Lei, Berend; Mendelson, Bryan Christopher
Abstract: The safety and effectiveness of facial cosmetic surgery procedures are dependent on detailed 3D understanding of the complex surgical anatomy of the face. Traditional, small sample size anatomical dissection studies have limitations in providing definitive clarification of the fascial layers of the face, and especially in their relationship with the facial nerve, and their reaction to surgical manipulation. The objective study of large tissue areas is required to effectively demonstrate the broader architecture. Conventional histology techniques were modified to handle extraordinarily large tissue samples to fulfill this requirement. Full‐thickness soft tissue samples (skin to bone) of maximum length 18 cm, width 4 cm, and tissue thickness 1 cm, were harvested from 20 hemifaces of 15 fresh human cadavers (mean age at death = 81 years). After fixation, the samples were processed with an automated processor using paraffin wax for 156 h, sectioned at 30 μm, collected on gelatin‐chromium‐coated glass slides, stained with a Masson's Trichrome technique and photographed. Using this technique, excellent visualization was obtained of the fascial connective tissue and its relationship with the facial mimetic muscles, muscles of mastication and salivary glands in 73 large histological slides. The resulting slides improved the study of the platysma and superficial musculo‐aponeurotic system (SMAS), the spaces and ligaments, the malar fat pad, and the facial nerve in relations to the deep fascia. Additionally, surgically induced changes in the soft‐tissue organization were successfully visualized. This technique enables improved insight into the broad structural architecture and histomorphology of large‐scale facial tissues.